The Importance of Office Layout for Employee Productivity - Ahmad, Nurbarirah; Jamin, Aziean; Beta, Raja Mayang Delima Mohd; Ismail, Shafinar; Sakarji, Siti Rosnita; Zain, Zainab Mohd (Dinamika Pendidikan, 2020)
This study was conducted to explain the impact of open and enclosed plan office layouts on employee productivity.Â  The subject area for this study was in Amanah Saham Pahang Berhad (ASPA). This study involved 52 respondents from Administration Department, Finance Department, Logging, Planning and development of Forest Department and Investment Department. Data collection method used a questionnaire, and descriptive analysis is used to data analysis. The results showed that the condition of employee productivity was in good condition, but the office layout did not affect employee productivity. Moreover, the results from the findings showed that only enclosed plan office had significant positive relationships and it answered research questions and supported the hypotheses presented in this research study.Â  As a conclusion, this research study helps the other researcher to explore the impact of office layout on employee productivity. This research study result was supported by previous results presented at every research finding.